Decarbonising the iron and steel industries: Production of carbon-negative direct reduced iron by using biosyngas. (1st April 2023) - Zaini, Ilman Nuran; Nurdiawati, Anissa; Gustavsson, Joel; Wei, Wenjing; Thunman, Henrik; Gyllenram, Rutger; Samuelsson, Peter; Yang, Weihong
Highlights: Different integration scenarios are proposed for DRI production using biosyngas. Mature fluidised bed gasifiers (TRLs 9) are considered for producing biosyngas. The novel biosyngas DRI route can compete with other existing and emerging routes. Carbon negative is possible as up to 1.13 t CO2 per t DRI can be captured and stored. Abstract: Bioenergy with carbon capture and storage (CCS) in iron and steel production offers significant potential for CO2 emission reduction and may even result in carbon-negative steel. With a strong ambition to reach net-zero emissions, some countries, such as Sweden, have recently proposed measures to incentivise bioenergy with CCS (BECCS), which opens a window of opportunities to enable the production of carbon-negative steel. One of the main potential applications of this route is to decarbonise the iron reduction processes that account for 85 % of the total CO2 emission in the iron and steel plants. In this study, gasification is proposed to convert biomass into biosyngas to reduce iron ore directly. Different cases of integrating the biomass gasifier, Direct Reduced Iron (DRI) shaft furnace, and CCS are evaluated through process simulation work. Based on the result of the work, the proposed biosyngas DRI route has comparable energy demand compared to other DRI routes, such as the well-established coal gasification and natural gas DRI route. The proposed process can also capture 0.65–1.13 t of CO2 per t DRI depending on the integration scenarios, which indicates a promising route to achieving carbon-negative steel production.